eGEMs: Pragmatic Publishing to Build a Learning Health System - Holve, Erin (EGEMS (Wash DC), 2012)
The Electronic Data Methods (EDM) Forum announces the launch of eGEMs (Generating Evidence and Methods to improve patient outcomes), a new, free, open access, peer-reviewed e-publication. eGEMs aims to disseminate innovative ideas about how electronic clinical data (ECD) can be leveraged in comparative effectiveness research (CER), patient-centered outcomes research (PCOR) and quality improvement (QI). eGEMs seeks submissions in four main topic areas: analytic methods, clinical informatics, governance, and the learning health system. The goal of eGEMs is ultimately to promote dialogue and the sharing of ideas between researchers and other stakeholders in a credible and timely way, extending the efforts of the EDM Forum.